Neuroprotective epi-drugs quench the inflammatory response and microglial/macrophage activation in a mouse model of permanent brain ischemia - Mota, Mariana (J Neuroinflammation, 2020)
BACKGROUND: Activation of NF-kappaB RelA deacetylated at the lysine residues, except the lysine 310, drives pro-apoptotic transcription in noxious brain ischemia. We showed that the sinergistic combination of the histone deacetilase inhibitor MS-275 with the sirtuin 1 activator resveratrol, at very low doses, restores normal RelA acetylation and elicit neuroprotection in mice subjected to transient middle cerebral artery occlusion (tMCAO) and primary cortical neurons exposed to oxygen-glucose-deprivation (OGD). The present study aims at corroborating the neuroprotective potential of the epigenetic treatment in a model of permanent brain ischemia and investigate its effect on post-ischemic inflammation and microglia activation. METHODS: Male mice subjected to permanent occlusion of the distal MCAO (pMCAO) were treated with vehicle or MS-275 (20 μg/kg) and resveratrol (680 μg/kg) i.p. immediately after the ischemia. Microglia-containing mixed glial cultures were prepared from the brain of 1–3-day-old mice. Primary cortical neurons were prepared from 15-day-old embryonic mice. RESULTS: MS-275 and resveratrol in combination, but not individually, reduced infarct volume and neurological deficits evaluated 48 h after the pMCAO. At 24 h, the treatment inhibited the RelA binding to Nos2 promoter, reduced the elevated expression of Nos2, Il6, Il1b, Mrc1 and Ym1 and the leukocytes infiltration in the ischemic area. The effect was nonpermanent. The treatment did not limit the sustained leukocyte infiltration or Nos2 and Il1b transcription observed at 7 days. Though, it induced alternative activation markers of microglia/macrophages, Arg1, Ym1 and Fcgr2b that could be added to Mrc1, Tgfb1 and Trem2 spontaneously increased at 7 days after ischemia. At 24 hours the drug treatment quenched the microglia/macrophages activation in the ischemic cortical sections, as shown by the recovered ramified morphology and lowered iNOS or CD68 immunoreactivity in Iba1-positive cells. Both microglia and astrocytes in mixed glial cultures, but not pure astrocytes, displayed signs of activation and iNOS-immunoreactivity when treated with a conditioned medium (NCM) from OGD-exposed cortical neurons. The epigenetic drugs limited the OGD-NCM-mediated activation. CONCLUSIONS: Our findings indicate that single treatment with MS-275 and resveratrol can reduce stroke-mediated brain injury and inflammation observed 2 days after the pMCAO and put the rational to test repeated administration of the drugs. The anti-inflammatory property of MS-275 and resveratrol combination can be ascribed to both primary direct inhibition of microglia/macrophage activation and secondary glial/macrophages inhibition mediated by neuroprotection. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12974-020-02028-4.